Clinical significance of clonal hematopoiesis in the setting of autologous stem cell transplantation for lymphoma. Issue 12 (26th September 2022) - Lackraj, Tracy; Ben Barouch, Sharon; Medeiros, Jessie J. F.; Pedersen, Stephanie; Danesh, Arnavaz; Bakhtiari, Mehran; Hong, Michael; Tong, Kit; Joynt, Jesse; Arruda, Andrea; Minden, Mark D.; Kuruvilla, John; et al.
Abstract: Autologous stem cell transplantation (ASCT) remains a key therapeutic strategy for treating patients with relapsed or refractory non‐Hodgkin and Hodgkin lymphoma. Clonal hematopoiesis (CH) has been proposed as a major contributor not only to the development of therapy‐related myeloid neoplasms but also to inferior overall survival (OS) in patients who had undergone ASCT. Herein, we aimed to investigate the prognostic implications of CH after ASCT in a cohort of 420 lymphoma patients using ultra‐deep, highly sensitive error‐correction sequencing. CH was identified in the stem cell product samples of 181 patients (43.1%) and was most common in those with T‐cell lymphoma (72.2%). The presence of CH was associated with a longer time to neutrophil and platelet recovery. Moreover, patients with evidence of CH had inferior 5‐year OS from the time of first relapse (39.4% vs. 45.8%, p  = .043) and from the time of ASCT (51.8% vs. 59.3%, p  = .018). The adverse prognostic impact of CH was not due to therapy‐related myeloid neoplasms, the incidence of which was low in our cohort (10‐year cumulative incidence of 3.3% vs. 3.0% in those with and without CH, p  = .445). In terms of specific‐gene mutations, adverse OS was mostly associated with PPM1D mutations (hazard ratio (HR) 1.74, 95% confidence interval (CI) 1.13–2.67, p  = .011). In summary, we found that CH is associated with an increased risk of non‐lymphoma‐related death after ASCT, which suggests that lymphoma survivors with CH may need intensified surveillance strategies to prevent and treat late complications. Abstract : Lymphoma patients with clonal hematopoiesis have a shorter overall survival following autologous stem cell transplantation.